Fock-space projection operators for semi-inclusive final states - Dickinson, Robert; Forshaw, Jeff; Millington, Peter (Elsevier, 2017)
We present explicit expressions for Fock-space projection operators that correspond to realistic final states in scattering experiments. Our operators automatically sum over unobserved quanta and account for non-emission into sub-regions of momentum space.